SOCIAL LIFE IN THE FERGANA VALLEY DURING THE PERIOD OF THE RUSSIAN EMPIRE - Xalimjon To‘xlibayevich Juraev (The Conference Hub, 2025)
This article examines the socio-cultural life of Turkestan, particularly the Fergana Valley, during the period of Russian imperial rule in the late nineteenth and early twentieth centuries. The study analyzes the colonial policies implemented by the Tsarist administration, the transformation of the local economy—especially agriculture—and the attitude of the indigenous population toward socio-cultural processes. Special attention is given to changes in education, religious life, publishing activities, and the emergence of the local press. The article also highlights the role of local intellectuals and religious scholars in preserving cultural identity and responding to colonial governance.
Keywords: Social life, books, newspapers, typography, colonialism, waqf, publishing, administration, supply, youth, politics.